Rol de enfermería en la gestión del riesgo en salud de los habitantes de calle - Amórtegui Ballén, María Alejandra; Ochoa Almanza, Nicole Julieth (Universidad Antonio Nariño, 2024)
The purpose of this research is to describe the health risk management of nurses towards the homeless population by means of a narrative review because the weak knowledge of the professionals when attending this population was identified. Objective: to describe the role of nurses in the health risk management of street dwellers. Methodology: a narrative review was conducted using Whittemore's five stages: identification of the problem, literature search, data evaluation, data analysis and presentation. The databases consulted and used through the Learning and Research Resource Center (CRAI) of the UAN were Nursing@Ovid®, LILACS, Pubmed, Scopus, between 2018 to 2024. Additionally, the Rayyan tool was used for the identification, screening, and selection of articles. Results: 918 articles were identified from the different databases, from which fifty-five duplicate records were eliminated, identifying a total of 895 selected for screening by title and abstract, adding six records manually identified from other sources. From these, 857 were excluded, obtaining 37 articles for the full text review, subsequently, 23 researches were excluded, because they did not talk about the nursing role, did not meet the inclusion criteria or were duplicated in the data of other articles. Finally, fourteen articles were selected and included in the review.